Understanding Elephant Disturbance in Human-Elephant Conflicts in Perak, Malaysia - Khairunizan, Huda Khalidah; Mohamad Abdullah, Nazirah (Enhanced Knowledge in Sciences and Technology, 2025)
Human-elephant conflict (HEC) has emerged as a significant challenge in North Peninsular Malaysia, driven by habitat fragmentation, agricultural expansion, and urbanization [1]. This study analyses temporal patterns of HEC from 2015 to 2021 using complaint data categorized into five disturbance types: BK (Berkeliaran), GK (Ganggu Ketenteraman), MK (Mendatangkan Ketakutan), RH (Rosakkan Harta Benda), and RT (Rosakkan Tanaman) [2]. By employing one-way ANOVA, the research investigates whether the mean number of complaints significantly differed across the years [3]. Results indicate no statistically significant differences in complaint frequencies over time, suggesting consistent patterns influenced by persistent conflict drivers rather than random fluctuations [4]. The lack of significant variation suggests that the factors driving HEC, such as habitat loss and human encroachment, have remained constant over the study period, reinforcing the need for long-term mitigation efforts [5]. Key limitations include reliance on historical data, broad categorization of disturbances, and a geographically constrained focus [6]. Recommendations for future research emphasize incorporating real-time data, refining disturbance categories, expanding the study region, and integrating qualitative insights to capture the socio-economic impacts of HEC [7]. This study contributes to the growing body of knowledge on HEC by providing evidence-based insights for policymakers and conservationists [8]. It highlights the need for long-term mitigation strategies, including resource allocation, habitat conservation, and community engagement [9]. The findings underscore the importance of coexistence approaches that balance human welfare with the conservation of endangered Asian elephants, fostering sustainable solutions to address this enduring conflict [10].